An amorphous perfluoropolymer, its preparation and use
Patent Information
- Application Number
- CN202611459419.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
该工艺存在多重固有缺陷:(1)氟气剧毒、强腐蚀,反应器需采用镍基特种合金,设备投入成本极高;(2)高温氟化能耗高、工艺流程长,生产成本显著上升;(3)高温氟化易造成高分子链断裂降解,产物发黄、分子量下降,并可能引入金属离子杂质,难以满足极紫外光刻(EUV)半导体高纯要求;(4)后氟化难以完全消除微量羧基残留,长期高温使用仍存在性能劣化风险
(1)端基稳定性大幅提升,省去氟化工序:全氟酰基类引发剂原位引入CnF2n+1-(n≥2)稳定全氟烷基端基,全氟端基占比最高可达99%以上,无需氨气中和与氟气高温氟化两步后处理;产物TGA 5%热失重温度≥360 ℃,优于传统氟化后产品(对比例1为340 ℃),且无酸性端基分解污染风险。
Smart Images

Figure CN122978331A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fluorine-containing polymer materials technology, specifically relating to an amorphous perfluoropolymer, its preparation method, and its application. Background Technology
[0002] Amorphous perfluoropolymers, with their advantages of high light transmittance, low refractive index, chemical resistance, and wide-temperature thermal stability, are core materials for optical waveguides, fiber optic cladding, photolithography mask protective films (Pellicles), and ultraviolet optical lenses. Representative products include: the TeflonAF series obtained by copolymerizing perfluoro-2,2-dimethyl-1,3-dioxane (PDD) with tetrafluoroethylene (TFE) (as disclosed in US Patent Application No. US53224274, Publication No. US3978030A), and the CYTOP series of homopolymers obtained by free radical cyclization polymerization of perfluoro(3-butenyl vinyl ether) (PBVE, structural formula CF2=CFOCF2CF=CF2) (as disclosed in US Patent Application No. US23382088, Publication No. US4897457A).
[0003] Current industrial processes primarily rely on free radical polymerization. For example, EP patent application number EP94203365 and publication number EP0645406B1 discloses an aqueous emulsion polymerization method for PDD and TFE binary copolymers, using inorganic hydrogen / oxygen-containing initiators such as ammonium persulfate (APS). These initiators, upon decomposition, generate unstable end groups such as -COOH, -COF, and -CF2H at the molecular chain ends. During high-temperature processing and photolithography, these initiators easily decompose and release acidic small molecules, leading to increased optical haze and semiconductor wafer contamination.
[0004] To eliminate unstable end groups, the industry generally uses a two-step post-processing process: first, ammonia / organic amines are used to neutralize the acyl fluoride end groups to convert them into amide intermediates, and then fluorine / fluorine-nitrogen mixed gas is introduced at a high temperature of 200-300℃ for deep fluorination to convert the end groups into a stable -CF3 structure (commercial products such as CYTOP series and fluorinated Teflon AF). This process has several inherent defects: (1) Fluorine gas is highly toxic and corrosive, and the reactor needs to use nickel-based special alloys, resulting in extremely high equipment investment costs; (2) High-temperature fluorination has high energy consumption and a long process flow, which significantly increases production costs; (3) High-temperature fluorination is prone to polymer chain breakage and degradation, resulting in yellowing of the product, a decrease in molecular weight, and the introduction of metal ion impurities, making it difficult to meet the high purity requirements of extreme ultraviolet lithography (EUV) semiconductors; (4) Post-fluorination is difficult to completely eliminate trace carboxyl residues, and there is still a risk of performance degradation after long-term high-temperature use.
[0005] Existing technologies also include a small number of PDD-PBVE and PDD-perfluoroalkyl vinyl ether copolymer systems, but they all use aqueous emulsion polymerization systems and still rely on fluorine gas for post-fluorination. The solvent systems mostly use CFC-113 chlorofluorocarbon solvents, which are ozone-depleting controlled substances and have poor environmental compliance. The single binary copolymer system has a narrow range of adjustable material properties and cannot simultaneously meet the diverse requirements such as low refractive index, high glass transition temperature, and excellent film-forming properties. Summary of the Invention
[0006] The first technical problem to be solved by the present invention is to provide an amorphous perfluoropolymer that does not require fluorine gas stabilization post-treatment, thereby improving product purity, in light of the current state of the prior art.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned amorphous perfluoropolymer, which does not require fluorine gas stabilization post-treatment and has good environmental compliance.
[0008] The third technical problem to be solved by the present invention is to provide an application of the above-mentioned amorphous perfluoropolymer.
[0009] The technical solution adopted by the present invention to solve the first technical problem mentioned above is: an amorphous perfluoropolymer, comprising repeating units derived from PDD and / or PBVE, wherein the molar percentage of perfluoroalkyl end groups with ≥2 carbon atoms in all end groups of the molecular chain is ≥95mol%, and the perfluoroalkyl end groups are formed in situ by the decomposition of residues from perfluoroacyl initiators during free radical polymerization, without stabilization treatment by fluorine gas or fluorine-nitrogen mixture.
[0010] It should be noted that existing products treated with fluorine gas after fluorination (such as the CYTOP series) have an end group of -CF3 (1 carbon atom); the iodine transfer living polymerization product has an end group of -CF2I (1 carbon atom); the polymer of this invention has an end group of perfluoroalkyl with ≥2 carbon atoms. These three can be clearly distinguished by their end group structures. 19 Quantitative identification by F NMR. This end group is formed in situ from the decomposition residues of perfluoroacyl initiators, requiring more than 2 carbon atoms to obtain a more stable initiator, which is beneficial to the stability of the polymer molecular weight.
[0011] Preferably, the molar percentage of unstable end groups in all end groups of the molecular chain is <1 mol%, and the unstable end groups include at least one of -COOH, -COF, -CONH2, -CF2H, and -CF2I.
[0012] Preferably, the perfluoroalkyl terminal group is C n F 2n+1 -, where n is an integer from 2 to 7.
[0013] Preferably, the perfluoroacyl initiator is a perfluorodiac peroxide or a perfluorosulfonyl peroxide suitable for polymerization at -20 to 50°C. The perfluorodiac peroxide has the general formula RfC(O)-OOC(O)Rf', where Rf and Rf' are each independently C2 to C7 straight-chain or branched perfluoroalkyl, or perfluoroalkyl containing ether oxygen bonds. The perfluorosulfonyl peroxide has the general formula RfSO2-OO-SO2Rf', where Rf and Rf' are each independently C1 to C8 (preferably C2 to C6) perfluoroalkyl or perfluoroalkyl containing ether oxygen bonds.
[0014] The perfluorodiac peroxide is preferably at least one of perfluoropropionyl peroxide (PFP), perfluorobutyryl peroxide (PFB), perfluoroglutaryl peroxide, perfluoroadiazine peroxide, and hexafluoropropylene oxide (HFPO) dimer peroxide, and is suitable for medium and low temperature polymerization.
[0015] Perfluorosulfonyl peroxide exhibits high initiation activity and high polymerization conversion rate.
[0016] The aforementioned perfluoroacyl initiators decompose to generate perfluoroalkyl radicals Rf·, which initiate monomer polymerization and form C in situ at the molecular chain ends. n F 2n+1 - (n≥2) Stable end bases.
[0017] Preferably, the comonomers forming the polymer are classified into three levels according to their molecular structure and function: First comonomer: at least one of PDD and PBVE; the first comonomer provides amorphousness, high glass transition temperature and ultraviolet transmittance; Second comonomer: One of tetrafluoroethylene (TFE) and trifluorochloroethylene (CTFE); the second comonomer is used to adjust the glass transition temperature, melt flowability and mechanical strength. The third comonomer is one of perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), or perfluoropropyl vinyl ether (PPVE). The third comonomer is used to regulate the refractive index and crystallinity, improve film-forming properties, and reduce optical haze. Of all the comonomers, the total molar percentage of the first comonomer is 50–100 mol% (preferably 60–95 mol%). When the first comonomer is PDD and PBVE, the molar ratio of PDD to PBVE is 1:10–10:1. The molar percentage of the second comonomer is 0–50 mol%, and the molar percentage of the third comonomer is 0–10 mol%, thereby forming homopolymers, binary copolymers, ternary copolymers, or quaternary copolymers.
[0018] This allows the polymer material of the present invention to have a wide range of adjustable properties, and can simultaneously meet diverse requirements such as low refractive index, high glass transition temperature, and excellent film-forming properties.
[0019] In the above embodiments, preferably, the number-average molecular weight (Mn) of the amorphous perfluoropolymer is 85,000–353,000, more preferably 120,000–300,000; the molecular weight distribution index (PDI) is 1.5–3.0, more preferably 1.8–2.5; the 5% thermal weight loss decomposition temperature under nitrogen atmosphere is ≥350℃; the visible light transmittance at 300–800 nm is >92%; and the film haze is <0.5%.
[0020] The technical solution adopted by the present invention to solve the second technical problem mentioned above is as follows: a method for preparing the amorphous perfluoropolymer as described above, comprising the following steps: Step 1, raw material dissolution: Under an inert atmosphere, the monomers are dissolved in a fluorocarbon solvent to prepare a homogeneous solution with a total monomer mass fraction of 10-50 wt%; the monomers include PDD and / or PBVE (i.e., the first comonomer mentioned above). Step 2, low-temperature free radical polymerization: add 0.1-5.0% of a perfluoroacyl initiator by mass of the total monomers, and react at a constant temperature of -20-50℃ (preferably -10-30℃) for 2-48 hours to obtain a reaction solution; Step 3, post-processing purification: The reaction solution is poured into a low-carbon alcohol (such as methanol or ethanol) or perfluoroalkane to precipitate the product. After filtration, it is dried under vacuum at 80–120°C to directly obtain a white polymer powder with perfluoroalkyl end groups. No high-temperature fluorination stabilization treatment with fluorine or a fluorine-nitrogen mixture is performed throughout the process.
[0021] Preferably, the fluorocarbon solvent is at least one of perfluorotertiary amines, perfluorocyclic ethers, perfluoropolyethers, hydrofluoroethers, and hydrofluorocarbon solvents. Specifically, the perfluorotertiary amine is at least one of perfluorotriethylamine, perfluorotributylamine, and perfluorotripentylamine; the perfluorocyclic ether is perfluoro(2-butyltetrahydrofuran); and the perfluoropolyether is at least one of low molecular weight linear perfluoropolyethers, branched perfluoropolyethers, and alkoxy-terminated perfluoropolyethers. The fluorocarbon solvent does not contain ozone-depleting chlorofluorocarbon solvents (such as trichlorotrifluoroethane, CFC-113).
[0022] In step one, the monomers may further include the aforementioned second and third comonomers. When introducing the second and third comonomers, each comonomer can be fed simultaneously at once or continuously in stages. During feeding, the ratio of the total molar amount of the second and third comonomers to the total molar amount of the first comonomer is 0:1 to 1:1. The uniformity of the copolymer composition along the molecular chain can be controlled by segmented continuous feeding.
[0023] Preferably, in step two, 0.01–1.0% of a perfluoroalkyl iodine chain transfer agent, CF3(CF2)nI, can be selectively added, where n is an integer from 1 to 6, to control the polymer's molecular weight distribution (PDI) to ≤2.5. This reduces the polymer's molecular weight and narrows its molecular weight distribution. The resulting polymer chain ends contain -CF2I end groups, which can be further functionalized through coupling, substitution, and other reactions to prepare telechelicer-type functional fluoropolymer intermediates.
[0024] The technical solution adopted by the present invention to solve the third technical problem mentioned above is: the application of the amorphous perfluoropolymer as described above, applied to protective films for optical components and semiconductor electronic devices.
[0025] Optical components such as: ultraviolet / visible lenses, optical waveguides, fiber cladding, deep ultraviolet (DUV) / extreme ultraviolet (EUV) anti-reflective coatings, and deep ultraviolet optical windows.
[0026] Protective films for semiconductor electronic devices include: Pellicle thin films (mask protection films) for photolithography masks, passivation protection layers on wafer surfaces, and precision optical carrier films.
[0027] The polymer material of this invention is free of metal ions and has no decomposable acidic end groups, making it well-suited for high-cleanliness and demanding production processes such as extreme ultraviolet lithography, and thus possessing value for large-scale industrial production.
[0028] Compared with the prior art, the advantages of the present invention are as follows: (1) Significantly improved end-group stability, eliminating the defluorination process: C is introduced in situ from perfluoroacyl initiators. n F 2n+1 - (n≥2) Stable perfluoroalkyl end groups, with perfluoro end group ratios reaching up to 99% or more, eliminating the need for two-step post-treatment of ammonia neutralization and high-temperature fluorination; the product's TGA 5% thermal weight loss temperature is ≥360 ℃, which is superior to traditional fluorinated products (Comparative Example 1 is 340 ℃), and there is no risk of acidic end group decomposition and contamination.
[0029] (2) Production safety and equipment investment are greatly reduced: The use of highly toxic and corrosive fluorine gas is completely avoided. There is no need for a high-pressure corrosion-resistant special alloy fluorination reactor. Production can be completed by low-temperature solution polymerization, and there are no safety hazards of explosion or toxic gas leakage.
[0030] (3) Reduced production costs and improved efficiency: The elimination of the ammonolysis and post-fluorination processes reduces overall energy consumption by more than 30% and shortens the production cycle by about 50%, facilitating continuous industrial production.
[0031] (4) High product purity: No aqueous emulsion system, no corrosion and leaching of metal equipment by fluorine gas, low content of polymer metal ion impurities and extractable acidic impurities, suitable for high-cleanliness semiconductor scenarios such as DUV and EUV lithography masks.
[0032] (5) Wide range of adjustable material properties: The three-level comonomers can be freely matched with homopolymers and binary / ternary / quaternary copolymers to continuously control the glass transition temperature Tg, refractive index, light transmittance and film-forming properties; a variety of perfluoroacyl initiators and environmentally friendly fluorocarbon solvents broaden the selection of raw materials; when combined with perfluoroalkyl iodine chain transfer agents, the molecular weight and distribution can be precisely controlled and functionalized iodine-containing end-group intermediates can be obtained. Attached Figure Description
[0033] Figure 1 The TGA thermogravimetric curves are shown for comparing the polymer prepared in Example 1 of this invention with those prepared in Comparative Example 1. Figure 2 The polymer prepared in Example 1 of this invention¹ 9 fluorine NMR spectrum; Figure 3 The curves show the effects of different amounts of perfluoroalkyl iodine chain transfer agent on polymer molecular weight and PDI. Detailed Implementation
[0034] The method for determining the polymer of the present invention is as follows: End group structure and molar ratio: adopted 19 Quantitative determination by fluoropolymer NMR. The polymer is dissolved in perfluorobenzene or perfluorotributylamine, with hexafluorobenzene as the internal standard for chemical shift, and the determination is performed on an NMR spectrometer at 400 MHz or higher. The molar percentage is calculated based on the integrated area of the characteristic chemical shift peaks of various end groups. The -CF3 signal of perfluoroalkyl end groups with ≥2 carbon atoms has a different chemical shift than the -CF3 signal of the main chain, and can be integrated and quantified separately.
[0035] Molecular weight and distribution: Gel permeation chromatography (GPC) was used with low molecular weight perfluoropolyether or perfluorotributylamine as the mobile phase at 40°C for determination. The determination was corrected with polymethyl methacrylate standard, or differential-multi-angle laser light scattering was used to determine the absolute molecular weight.
[0036] 5% decomposition temperature due to thermogravimetric analysis (TGA), nitrogen atmosphere, heating rate 10℃ / min, temperature range: room temperature to 600℃.
[0037] Transmittance and haze: The polymer solution was cast or hot-pressed into a film with a thickness of approximately 100 μm, and the transmittance and haze were measured at 300–800 nm according to ASTM D1003. Glass transition temperature Tg: Differential scanning calorimetry (DSC) was performed under a nitrogen atmosphere at 10 °C / min.
[0038] The following are specific examples:
[0039] Example 1
[0040] This embodiment uses perfluorobutyryl peroxide as an initiator, PBVE homopolymerization, and FC-75 solvent, as detailed below: A 250 mL low-temperature three-necked flask was magnetically stirred, and 50 g of perfluoro(2-butyltetrahydrofuran) (FC-75) and 30 g of PBVE monomer were added. The mixture was purged with nitrogen three times. The temperature was lowered to 0 °C, and 0.3 g of perfluorobutyryl peroxide (PFB) was added. The mixture was stirred at a constant temperature of 0–5 °C for 12 h. The reaction solution was slowly poured into 500 mL of methanol to precipitate the product. After filtration, the product was dried under vacuum at 80 °C for 12 h to obtain 28.2 g of white, fluffy powder, which was the desired amorphous perfluoropolymer, with a polymerization yield of 94%.
[0041] Polymer performance testing: Mn=120000, PDI=2.1; and as... Figure 2 As shown, 19 F NMR only detected the -C3F7 perfluorinated end group signal, with no unstable -COOH or -COF end groups; the proportion of perfluorinated alkyl end groups with ≥2 carbon atoms was >99%; TGA 5% weight loss temperature was 365 ℃. Figure 1 As shown. Tg=108℃, transmittance of 93% at 300~800 nm.
[0042] Example 2
[0043] This embodiment uses perfluoroglutaryl peroxide as an initiator, PDD-TFE binary copolymerization, and FC-43 solvent, as detailed below: In a 500 mL autoclave, 100 g of perfluorotributylamine (FC-43), 60 g of PDD, and 2.0 g of tetrafluoroethylene (TFE) were added (PDD to TFE molar ratio approximately 12:1). The mixture was cooled to -10 °C, and 0.5 g of perfluoroglutaryl peroxide was added. The reaction was carried out at -10 to 0 °C for 18 h. After depressurization, the mixture was precipitated with methanol and dried to obtain 56.5 g of copolymer, with a yield of 91%.
[0044] Polymer performance testing: Mn=180000, PDI=1.9; 19 Unstable oxygen-containing end groups were not detected by F NMR; Tg=160℃, TGA 5% weight loss temperature 370℃, transmittance of 300~800nm >92%.
[0045] Example 3
[0046] The preparation process in this embodiment is basically the same as that in Example 1, except that 0.15g of perfluorohexyl iodine C6F is added in this embodiment. 13I (0.5% of monomer mass), with other conditions unchanged, yielded 27.8 g of product, with a yield of 93%.
[0047] Polymer performance testing: Mn=85000, PDI=1.8, lower molecular weight and narrower molecular weight distribution; 19F NMR detected -C3F7 and -C6F. 13 Perfluoroalkyl and -CF2I terminal signals, wherein the iodine terminal can be further functionalized through coupling and substitution reactions.
[0048] Example 4
[0049] This embodiment uses HFPO dimer peroxide as an initiator, PDD-PBVE binary copolymerization, and a perfluoropolyether solvent, as detailed below: In a 500 mL autoclave, 120 g of low molecular weight perfluoropolyether solvent, 70 g of PDD, and 8.0 g of PBVE (PDD to PBVE molar ratio approximately 10:1) were added. The mixture was cooled to -15 °C, and 0.4 g of hexafluoropropylene oxide (HFPO) dimer peroxide was added. The reaction was carried out at a constant temperature for 20 h. Methanol precipitation and drying were performed to obtain 71.8 g of the product, with a yield of 92%.
[0050] Polymer performance testing: Mn=150000, PDI=2.0; Perfluoroalkyl end groups with ≥2 carbon atoms account for 99.2%; Tg=168℃; 300~800 nm transmittance 93.5%.
[0051] Example 5
[0052] This embodiment uses a compound solvent of perfluorotriethylamine and perfluoropolyether to achieve a ternary copolymerization of PDD-TFE-PPVE, as detailed below: The solvent is a 1:1 mass mixture of perfluorotriethylamine and low molecular weight perfluoropolyether, with 300g added; 65g PDD, 4g TFE, and 6g PPVE are added; 0.5g perfluorobutylsulfonyl peroxide is selected as the initiator, and the reaction is carried out at 0℃ for 14h. After methanol precipitation and vacuum drying, a ternary amorphous copolymer is obtained.
[0053] Polymer performance testing: TGA 5% weight loss temperature 372℃, film haze 0.3%.
[0054] Example 6
[0055] This embodiment uses perfluorotributylamine solvent and a quaternary copolymer of PDD-PBVE-CTFE-PMVE, as detailed below: 300g of perfluorotributylamine (FC-43) solvent was added to an autoclave, along with 50g each of four monomers: PDD, PBVE, CTFE, and PMVE. 0.5g of perfluorohexylsulfonyl peroxide was used as an initiator. Polymerization was carried out at -5℃ for 16 hours. After precipitation and drying, a quaternary amorphous copolymer was obtained. The product exhibits high light transmittance, low refractive index, and film-forming properties, making it suitable for use as an anti-reflective coating for optical waveguides.
[0056] Example 7
[0057] This embodiment uses low-temperature long-time polymerization to prepare high molecular weight PDD homopolymer, as detailed below: The preparation process in this embodiment is basically the same as that in Example 1, except that in this embodiment, the monomer is replaced with PDD, the reaction temperature is reduced to -20℃, the reaction time is extended to 72h, and the amount of initiator is reduced to 0.08g; 24.3g of polymer is obtained, with a yield of 81%.
[0058] Polymer performance testing: Mn=353000, PDI=2.8; 19 F NMR analysis confirmed that the percentage of perfluoroalkyl end groups with ≥2 carbon atoms was >99%, and no impurity end groups were detected.
[0059] Example 8
[0060] This embodiment uses HFPO dimer peroxide as an initiator, PDD-PBVE binary copolymerization, and a perfluoropolyether solvent, as detailed below: In a 500 mL autoclave, 150 g of low molecular weight perfluoropolyether solvent, 8.0 g of PDD, and 80 g of PBVE (PDD to PBVE molar ratio approximately 1:10) were added. The mixture was cooled to -15 °C, and 0.5 g of hexafluoropropylene oxide (HFPO) dimer peroxide was added. The reaction was carried out at a constant temperature for 20 h. Methanol precipitation and drying were performed to obtain 81.4 g of the product, with a yield of 92%.
[0061] Polymer performance testing: Mn=235000, PDI=1.9; 19 F NMR confirmed that the proportion of perfluoroalkyl end groups with ≥2 carbon atoms was >99%, and no unstable end groups such as -COOH and -COF were detected; Tg=116℃, TGA 5% weight loss temperature was 362℃, and transmittance of 300~800nm was 93%.
[0062] Comparative Example 1
[0063] This comparative example uses a traditional aqueous emulsion polymerization + fluorination process, as detailed below: 500g of deionized water, 20g of perfluoro-2,5-dimethyl-3,6-dioxanonate ammonium salt emulsifier, and 100g of PDD monomer were added to a stainless steel high-pressure reactor. The reactor was purged with nitrogen three times, heated to 40℃, and 1.0g of ammonium persulfate (APS) initiator was added. The reactor was kept at a constant temperature for 8 hours. The mixture was then cooled, demulsified, filtered, and dried to obtain coarse polymer powder.
[0064] polymer coarse powder 19 F NMR characterization: Approximately 60% of the terminal groups are -COOH, approximately 30% are -COF, and only about 10% are stable perfluoroalkyl terminal groups.
[0065] Post-treatment of polymer coarse powder: Tube furnace treatment at 250℃ with a 10% fluorine / nitrogen mixture for 6 hours (ammonia pretreatment for 2 hours); the final product has approximately 95% perfluorinated end groups (-CF3), but molecular weight degradation of approximately 15%, material yellowing, and a TGA 5% weight loss temperature of 340℃. Figure 1 As shown.
[0066] The amorphous perfluoropolymers prepared in the various embodiments of the present invention have stable perfluoroalkyl ends, are free of acidic impurities, have excellent thermal stability, and high ultraviolet transmittance. They can be processed into: (1) optical components: deep ultraviolet optical lenses, planar waveguides, communication fiber cladding, anti-reflective coatings for DUV / EUV equipment, and optical windows; (2) semiconductor electronic protective films: Pellicle ultra-thin protective films for photolithography masks, passivation films on wafer surfaces, and precision optical carrier films. The materials have low metal ion impurity content and no decomposable acidic end groups, making them suitable for high-cleanliness and stringent processes such as extreme ultraviolet lithography. Moreover, the preparation process does not require fluorine post-treatment, and the solvents are environmentally friendly and compliant, making them valuable for large-scale industrial production.
[0067] And such as Figure 3 As shown, with the increase of the perfluoroalkyl iodine chain transfer agent from 0 to 0.6 mol%, the chain transfer effect is enhanced, the weight-average molecular weight (Mw) of the polymer decreases significantly, and the molecular weight distribution (PDI) gradually narrows. When the chain transfer agent dosage exceeds 0.6 mol%, the concentration of iodine-terminated free radicals in the system becomes too high, resulting in a small amount of free radical coupling side reactions, further decreasing the molecular weight, but the PDI actually widens slightly. Considering both molecular weight and distribution, the preferred dosage range for the chain transfer agent in this system is 0.4–0.6 mol.
Claims
1. An amorphous perfluoropolymer comprising repeating units derived from PDD and / or PBVE, characterized in that: Of all the end groups of the molecular chain, the molar percentage of perfluoroalkyl end groups with ≥2 carbon atoms is ≥95 mol%, and the perfluoroalkyl end groups are formed in situ by the decomposition of residues during free radical polymerization by perfluoroacyl initiators, without stabilization treatment by fluorine gas or fluorine-nitrogen mixture.
2. The amorphous perfluoropolymer according to claim 1, characterized in that: Of all the end groups of the molecular chain, the molar percentage of unstable end groups is <1 mol%, and the unstable end groups include at least one of -COOH, -COF, -CONH2, -CF2H, and -CF2I.
3. The amorphous perfluoropolymer according to claim 1, characterized in that: The perfluoroalkyl terminus is C n F 2n+1 -, where n is an integer from 2 to 7.
4. The amorphous perfluoropolymer according to claim 1, characterized in that: The perfluoroacyl initiator is a perfluorodiac peroxide or a perfluorosulfonyl peroxide suitable for polymerization at -20 to 50°C. The perfluorodiac peroxide has the general formula RfC(O)-OOC(O)Rf', where Rf and Rf' are each independently C2 to C7 straight-chain or branched perfluoroalkyl, or perfluoroalkyl containing ether oxygen bonds. The perfluorosulfonyl peroxide has the general formula RfSO2-OO-SO2Rf', where Rf and Rf' are each independently C1 to C8 perfluoroalkyl or perfluoroalkyl containing ether oxygen bonds.
5. The amorphous perfluoropolymer according to claim 1, characterized in that: The comonomers that form the polymer are classified into three levels: First comonomer: at least one of PDD and PBVE; The second comonomer: one of tetrafluoroethylene (TFE) and chlorotrifluoroethylene (CTFE); The third comonomer is one of perfluoromethyl vinyl ether PMVE, perfluoroethyl vinyl ether PEVE, and perfluoropropyl vinyl ether PPVE. Of all the comonomers, the total molar percentage of the first comonomer is 50–100 mol%, and when the first comonomer is PDD and PBVE, the molar ratio of PDD to PBVE is 1:10–10:1; the molar percentage of the second comonomer is 0–50 mol%, and the molar percentage of the third comonomer is 0–10 mol%, thus forming homopolymers, binary copolymers, ternary copolymers, or quaternary copolymers.
6. The amorphous perfluoropolymer according to any one of claims 1 to 5, characterized in that: The amorphous perfluoropolymer has a number-average molecular weight (Mn) of 85,000 to 353,000; a molecular weight distribution index (PDI) of 1.5 to 3.0; a 5% thermal weight loss decomposition temperature ≥ 350℃ under nitrogen atmosphere; a visible light transmittance of 300–800 nm > 92%; and a film haze < 0.5%.
7. A method for preparing an amorphous perfluoropolymer as described in any one of claims 1 to 6, characterized in that... The steps are as follows: Step 1, raw material dissolution: Under an inert atmosphere, the monomer is dissolved in a fluorocarbon solvent to prepare a homogeneous solution with a total monomer mass fraction of 10-50 wt%; the monomer includes PDD and / or PBVE; Step 2, low-temperature free radical polymerization: add 0.1-5.0% of a perfluoroacyl initiator by weight of the total monomer, and react at a constant temperature of -20 to 50°C for 2-48 hours to obtain a reaction solution; Step 3, post-processing purification: Pour the reaction solution into a low-carbon alcohol or perfluoroalkane to precipitate, filter, and then vacuum dry at 80-120℃ to directly obtain a white polymer powder with perfluoroalkyl end groups.
8. The preparation method according to claim 7, characterized in that: The fluorocarbon solvent is at least one of perfluoro tertiary amines, perfluorocyclic ethers, perfluoropolyethers, hydrofluoroethers, and hydrofluorocarbon solvents. Among them, the perfluoro tertiary amine is at least one of perfluorotriethylamine, perfluorotributylamine, and perfluorotripentylamine; the perfluorocyclic ether is perfluoro(2-butyltetrahydrofuran); and the perfluoropolyether is at least one of low molecular weight linear perfluoropolyether, branched perfluoropolyether, and alkoxy-terminated perfluoropolyether.
9. The preparation method according to claim 7, characterized in that: In step two, a perfluoroalkyl iodine chain transfer agent, CF3(CF2)nI, accounting for 0.01 to 1.0% of the total monomer mass, may be selectively added to control the polymer molecular weight distribution (PDI) to ≤2.
5.
10. An application of the amorphous perfluoropolymer as described in any one of claims 1 to 6, characterized in that: It is used as a protective film for optical components and semiconductor electronic devices.
Citation Information
Patent Citations
Amorphous copolymers of perfluoro-2,2-dimethyl-1,3-dioxole
EP0645406B1
Polymers of fluorinated dioxoles
US3978030A
Novel fluorine-containing cyclic polymer
US4897457A